Enriquecimento ambiental: concepções, vivências e experiências dos biólogos em formação da UFSCar – São Carlos - Moraes, Lucas Tomazella (Universidade Federal de São Carlos, 2021)
Promoting a better quality of life for animals in captivity is extremely important to ensure the success of species conservation in zoos and aquariums, in addition to promoting awareness of visitors to environmental conservation. In this sense, the biologist under education needs to know practices that favor animal welfare, in order to apply and propagate the appropriate environmental awareness involved, such as Environmental Enrichment. The present work sought to analyze the conceptions and experiences that biologists under education have in relation to Environmental Enrichment. From the application of an online questionnaire with 50 students, containing open and closed and in Likert scale format questions, it was possible to understand ideas about the relationship between Environmental Enrichment and undergraduate disciplines, about students' understanding of the concepts needed in practice and its use as a means of promoting Environmental Education. The results obtained pointed to a positive relationship between knowing Environmental Enrichment and the number of subjects attended. It was also evident the importance that students give to animal welfare and the need to promote it in captive environments, in addition to its recognition as an important means to promote Environmental Education. However, it is necessary to highlight the urge for further research with a larger sample of both undergraduate students, as of non-academic people, in order to achieve a greater understanding of how this subject is seen by population in general. Finally, the high stakes from this work permeate its use for other research involving concepts related to Environmental Enrichment or Environmental Education, as for an incentive for education and awareness regarding animal welfare and species conservation in formal and informal teaching environments, seeking to provide conditions for the construction of an environmentally critical citizen.
Environmental enrichment: conceptions and experiences of biologists in formation at UFSCar – São Carlos
Keywords: Enriquecimento Ambiental; Conservação; Bem-estar animal; Educação Ambiental; Environmental Enrichment; Conservation; Animal welfare; Environmental Education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM